1993
DOI: 10.1165/ajrcmb/8.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Effects of Histamine on Proliferation of Lung- and Blood-derived T-Cell Clones from Healthy and Asthmatic Persons

Abstract: We have studied the effects of histamine on the proliferation and the intracellular cyclic adenosine monophosphate (cAMP) levels of T-lymphocyte clones (TLC) generated from bronchoalveolar lavage fluid (BALF) or peripheral blood (PB) from healthy and asthmatic persons. TLC from either compartment and from both groups of donors were heterogeneous in their response to histamine. In BALF-derived TLC, three types of responses were observed: histamine inhibited, stimulated, or did not modulate the anti-CD3-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We deliberately chose to use a polyclonal stimulus that induced cytokine production but that was not associated with a strong proliferative response [17,29]. Indeed, the proliferation of TCC was very low following stimulation, and was not significantly influenced by the addition of histamine (not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We deliberately chose to use a polyclonal stimulus that induced cytokine production but that was not associated with a strong proliferative response [17,29]. Indeed, the proliferation of TCC was very low following stimulation, and was not significantly influenced by the addition of histamine (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Histamine, in vitro, can stimulate alveolar macrophages to induce the release of b-glucuronidase [13], modify their phenotype [14] and activate bronchial epithelial cells [15] or eosinophils [16]. Histamine has been shown to reduce mitogen-induced T cell proliferation through its H 2 -receptor [17] and to inhibit the production of IL-2 and IFN-g by polyclonal agent-activated human peripheral blood mononuclear cells (PBMC) via H 2 -receptors [18]. Histamine appeared to act directly on T cells without accessory cell involvement [19].…”
Section: Introductionmentioning
confidence: 99%
“…For T cells expressing H2R, it was shown that the histamine-induced cAMP pathway mobilizes protein kinase A (PKA), which negatively regulates T cell proliferation [87] by down-regulation of IL-2 and IFN-g [95,96] and by increased IL-10 production [97]. This could also be shown for T cells isolated from asthmatic patients [98]. We recently demonstrated that histamine enhances the responsiveness of Th2 cells to TGF-b in an H2R-dependent fashion, resulting in more efficient IL-4 suppression by TGF-b [99].…”
Section: Adjuvants In Sit: Anti-histamines and Other Non-steroidal Anmentioning
confidence: 91%
“…In mast‐cell deficient mice there is no influx of mononuclear cells into the mucosal tissue after local IgE‐mediated reactions 12 . Furthermore, mast‐cell mediators like histamine and prostaglandins, and mast‐cell derived cytokines modulate T‐cell proliferation and cytokine production 11,13–15 . Interestingly, mast cells derived from the nasal mucosa of patients with allergic rhinitis may release IL‐4 by which they may contribute to ongoing IgE production and allergic reactions 16 …”
Section: Introductionmentioning
confidence: 99%
“…We have earlier reported on the effects of the mast‐cell mediator histamine on human T cells. Histamine enhanced or inhibited T‐cell proliferation and cytokine production dependent on the cell type studied and conditions applied 14,15 . To obtain information on the influence of the whole spectrum of mast‐cell products on T cells we have extended our studies and used the human mast cell line HMC‐1 as a model for mast cells 17 .…”
Section: Introductionmentioning
confidence: 99%